Whither Tanzania - Miti, Katabaro (Delhi : Ajanta Publications (India) : Distributors Ajanta Book International, 1987)
Articles on economic and political developments of Tanzania after her independence in 1961.
Includes bibliographies and index.
Keywords: Tanzania -- Politics and government -- 1964-; Tanzania -- Economic conditions -- 1964-